2023
DOI: 10.7717/peerj.14510
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of math anxiety, science anxiety, and gender on arts versus sciences choices in Qatari secondary schools

Abstract: Previous studies showed small-to-moderate associations between students’ performances in math and science and math anxiety and science anxiety, respectively. Accordingly, the high prevalence of these two forms of topic anxiety represent severe obstructions to the worldwide demand calling for improving the quality of math and science achievements and, subsequently, increasing career success in science, technology, engineering, and math (STEM) domains. Therefore, this study examined math anxiety and science anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 50 publications
(84 reference statements)
1
12
0
1
Order By: Relevance
“…Any intervention would not be possible unless an accurate assessment is provided using a reliable measure with adequate psychometric proprieties. This is particularly important for high school students who might have a broader repertoire of negative experiences in math (e.g., for a review see Ashcraft et al, 2007 ), especially because high levels of math anxiety was found to be a critical factor for avoiding STEM-related courses and careers ( Megreya and Al-Emadi, in press ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any intervention would not be possible unless an accurate assessment is provided using a reliable measure with adequate psychometric proprieties. This is particularly important for high school students who might have a broader repertoire of negative experiences in math (e.g., for a review see Ashcraft et al, 2007 ), especially because high levels of math anxiety was found to be a critical factor for avoiding STEM-related courses and careers ( Megreya and Al-Emadi, in press ).…”
Section: Discussionmentioning
confidence: 99%
“…Math anxiety refers to the feelings of fear, tension, and apprehension upon exposure to math-related materials during learning and assessment, which elicit a range of personal, educational, and cognitive consequences ( Ashcraft, 2002 ). For example, individuals with high levels of math anxiety tend to avoid math subjects at school and university levels, consequently influencing their prospective career choices and performance in everyday life activities ( Moustafa et al, 2020 ; Megreya and Al-Emadi, in press ). According to the Organization for Economic Co-operation and Development’s report, the prevalence rate of math anxiety in 15-year old students is 30% ( OECD, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, MA was previously found to strongly correlate with general anxiety and test anxiety (e.g. Megreya & Al-Emadi, 2023). Therefore, students in Arabic F I G U R E 3 The frequency percentages of low, moderate and high MA students for each item on the m-AMAS using the whole sample.…”
Section: Itemsmentioning
confidence: 97%
“…Future studies need to examine the prevalence of MA among primary school children using more than one scale across different countries. Nevertheless, this is the first study to examine MA using very large samples of students, representing about 17% of student population from Grades 7 to 12 in Qatar, using one of the most common scales of MA (m-AMAS), which has been validated in several cultures including Middle Eastern Arabic speaking countries (Megreya & Al-Emadi, 2023). Future studies could aim at a direct comparison of samples from different culture spaces.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation